How are Sustainability Disclosures by Smart Cities, Symbolic or Substantive? - Rani, Wahyu Mustika; Pujiningsih, Sri; Maharani, Satia Nur (Jurnal Akuntansi Aktual, 2026)
Purpose: This study aims to understand the themes of sustainability disclosure by smart cities in Indonesia through the lens of legitimacy theory. Method: We analyzed 199 sustainability disclosure narratives and visuals from 24 smart cities in Indonesia using content analysis. Meanwhile, legitimacy theory was used as an analytical tool to identify substantive and symbolic disclosures. Findings: Sustainability disclosures by smart cities are dominated by reports on environmental programs and commitments. Meanwhile, sustainability disclosures are mostly substantive (69%) rather than symbolic (31%). Originality/Value: This study provides new insights into sustainability disclosure in the context of smart cities in Indonesia, using textual and visual sources and the lens of legitimacy theory.